2019
DOI: 10.1101/840553
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BDKANN - Biological Domain Knowledge-based Artificial Neural Network for drug response prediction

Abstract: MotivationOne of the main goals of precision oncology is to predict the response of a patient to a given cancer treatment based on their genomic profile. Although current models for drug response prediction are becoming more accurate, they are also ‘black boxes’ and cannot explain their predictions, which is of particular importance in cancer treatment. Many models also do not leverage prior biological knowledge, such as the hierarchical information on how proteins form complexes and act together in pathways.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The data-rich nature of preclinical pharmacogenomics datasets has paved the way for the development of machine learning approaches to predict drug sensitivity in vitro and in vivo [25][26][27]. These computational approaches range from simple linear regression models [28,29] Lasso [30], and Elastic Net [31] to Random Forest [32], kernel-based models [33][34][35][36], highly non-linear models based on Deep Neural Networks [37][38][39][40][41][42][43][44], and most recently, reinforcement learning [45], few-shot learning [46], and multi-task learning [47]. These methods often take gene expression as input and predict the area above/under the dose-response curve (AAC/AUC) or half-maximal inhibitory concentration (IC50), the concentration of the drug that reduces the viability by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…The data-rich nature of preclinical pharmacogenomics datasets has paved the way for the development of machine learning approaches to predict drug sensitivity in vitro and in vivo [25][26][27]. These computational approaches range from simple linear regression models [28,29] Lasso [30], and Elastic Net [31] to Random Forest [32], kernel-based models [33][34][35][36], highly non-linear models based on Deep Neural Networks [37][38][39][40][41][42][43][44], and most recently, reinforcement learning [45], few-shot learning [46], and multi-task learning [47]. These methods often take gene expression as input and predict the area above/under the dose-response curve (AAC/AUC) or half-maximal inhibitory concentration (IC50), the concentration of the drug that reduces the viability by 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible future direction is to incorporate domain-expert knowledge into the structure of the model. A recent study has shown that such a structure improves the drug response prediction performance on cell line datasets and, more importantly, provides an explainable model as well ( Snow et al , 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Velodrome can also be extended to incorporate additional information about the drug, such as the chemical representation, to improve the performance (Jiang et al 2020). Finally, we did not discuss the explainability of the Velodrome model, but we note that the feature extractor of Velodrome can be replaced by a knowledge-based network (Snow et al 2020) to offer explainability and transparency (Yu et al 2018). A major limitation of our work is the output space discrepancy between cell lines, PDX samples, and patients, because on cell lines the drug response is measured based on the concentration of the drug but on PDX samples and patients the response is measured based on the change in the tumor volume after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Various methods of transfer learning have been proposed in the context of drug response prediction. These methods either address these discrepancies implicitly (Sharifi- Noghabi et al 2019;Snow et al 2020;Kuenzi et al 2020), or explicitly which means they assume that the model has access to the desired labeled or unlabeled target domain during training (Sharifi-Noghabi et al 2020;Mourragui et al 2019Mourragui et al , 2020Ma et al 2021;Zhu et al 2020;Warren et al 2020;Peres da Silva, Suphavilai, and Nagarajan 2021).…”
Section: Introductionmentioning
confidence: 99%